Dressed for leisure: the fashiondescriptions in the mondaine chronicles of João do Rio (ModaPalavra e-periódico, 2020)
In recent historiography, there is a consensus that themodernizing reforms promoted in Rio de Janeiro at thebeginning of the 20th century have changed the capital’sarchitecture and the relationship between its population andthe urban experience, introducing new practices into dailylives of cariocas. Among them was the introduction ofsports, with the press being the main vehicle for itsdissemination. This article explores the presence offashiondedicated to sports in chronicles and examines itscontribution to the validation of a collective imaginationabout leisure. The literary representation of sportswear gainscomplexity in the“civilisation du journal”, in which socialrelations are regulated by the production and reading ofmagazines. Therefore, the aim is to map out the access tofashionparadigms by readers of periodicals. As a case study,two chronicles of João do Rio on the sports theme areanalyzed. Published in the column“ASemana Elegante”in1916, they focus on the female presence and their clothingin the practice of tennis and sea bathing. We conclude thatthe importation and representation of sports practices andtheirfashionacted in the construction of an imaginary ofelegance in the city of Rio de Janeiro.
Keywords: Literature; Chronicle; João do Rio; Fashion